Improving visitor satisfaction in Egypt’s Heliopolis historical district - Hisham Abusaada (SpringerOpen, 2021)
Abstract This study employed applied thematic analysis (ATA) and importance-performance analysis (IPA) to measure visitor satisfaction in city streets. Forty-two elements that significantly influence visitors’ responses to streets and environments were included in five groups characterised by circumstances, characteristics, and indicators. Ibrahim Al-Lakani Street’s atmosphere satisfaction was measured by using coherent research methods. This investigation can assist designers in developing the morphological and social composition necessary to restore a street’s atmosphere and visitor satisfaction. This study contributes to the literature in two ways. First, it examines the relationships between street characteristics and visitor satisfaction in city streets regarding situations, atmospheres and social characteristics that shape these streets. Second, this study integrates ATA and IPA to create a tool for evaluating the significance, performance, and satisfaction of street situations, socio-morphological characteristics and street and visitor responses.